PROFESSIONALISM IN THE RECEPTION IN SUPPORTING THE FAIR OPERATIONS AT THE ZURI HOTEL - Wiwik Puspita; Sulaiman Helmi (Jurnal Ekonomi, 2022)
Professionalism is an employee's work attitude in which he conducts his job with skills, expertise, sincerity, correctness, and discipline in accordance with his field of competence by following the norms of the professional code of ethics that apply in his environment. This research focuses on understanding receptionist professionalism in order to assist the efficient running of The Zuri Hotel. A qualitative case study research approach was applied. Interviews and observations were employed as instruments. The study's findings indicate that the receptionist at The Zuri hotel plays a critical role since it is the hub of activity, taking care of accepting visitors who will stay, visitors who come from outside of the hotel, and all guests who seek information about the hotel. The author also discovered that, despite the receptionist's professionalism and adherence to standard operating procedures, there were nonetheless guest complaints concerning the check-in and check-out processes. Activities or actions that take care of the filming process of visitor IDs are also carried out at the reception, as is the completion of guest data while staying at the hotel, all of which are performed out professionally